Andris Nelsons conducts Debussy, Britten, and Rachmaninov -- With Ian Bostridge Royal Concertgebouw Orchestra - Debussy, Claude; Britten, Benjamin; Rachmaninov, Sergei (Royal Concertgebouw - Unitel, 2014)
The Six Épigraphes antiques are six miniatures for piano composed by Debussy in 1914, with parts of the music having been written in 1901 to accompany the Chansons de Bilitis by his friend, poet Pierre Louÿs. In 1977, Dutch composer Rudolf Escher transcribed a version for orchestra, impeccably rendered here by the Royal Concertgebouw Orchestra under Andris Nelsons! "J'ai seul la clef de cette parade sauvage" ("I alone have the key to this savage parade"): this final line of Arthur Rimbaud's poem Parade became the structuring motif in Benjamin Britten's cycle Les Illuminations, who--aged just 25--took up the challenge of setting Rimbaud's collection of prose poems to music. The marvelous RCO accompanies English tenor Ian Bostridge, paying homage to the great English composer for his 100th birthday. Finally, the evening is rounded out by a dynamite rendition of Rachmaninov's final major work: the self-referential and ecclesiastically-inspired Symphonic Dances, brimming with nostalgia and lush harmonies
Keywords: concert; Internet videos